The Influence of Good Corporate Governance (GCG), Profitability and Corporate Social Responsibility (CSR) on Company Value: Literature Review - Kalangi, Meyti Hanna Ester (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Good Corporate Governance (GCG), profitability, and Corporate Social Responsibility (CSR) are three important aspects in modern company management. GCG emphasizes transparency, accountability and fairness in decision making and company management. Profitability refers to a company's ability to generate profits. CSR refers to a company's commitment to providing a positive impact on society and the environment. The Literature Review article on the influence of GCG, profitability and CSR on company value is a scientific article which aims to build a research hypothesis on the influence between variables that will be used in further research. The method for writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) GCG influences company value 2) Profitability influences company value 3) CSR influences company value.